Peran Guru Pendamping dalam Meningkatkan Motivasi Belajar Pendidikan Agama Islam Anak Berkebutuhan Khusus di Sekolah Inklusi (SMP Muhammadiyah 1 Kartasura) - Hana Ayu Safitri; Mahasri Shobahiya (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study examines the role of special assistant teachers (GPK) in increasing motivation to learn Islamic Religious Education (PAI) for children with special needs (ABK) at SMP Muhammadiyah 1 Kartasura. Using a qualitative case study approach, data were collected through interviews, observations, and document studies. The results indicate that GPK plays an important role in increasing motivation to learn Islamic Religious Education for children with special needs by modifying materials, providing individual assistance, creating an adaptive learning atmosphere, and implementing rewards, educational games, and an emotional approach. GPK also acts as a mediator between PAI teachers, students, and parents. These findings confirm that the presence of GPK significantly contributes to increasing motivation to learn Islamic Religious Education for children with special needs.